C188-9, a specific inhibitor of STAT3 signaling, prevents thermal burn-induced skeletal muscle wasting in mice - Ono, Yuko; Saito, Masafumi; Sakamoto, Kazuho; Maejima, Yuko; Misaka, Shingen; Shimomura, Kenju; Nakanishi, Nobuto; Inoue, Shigeaki; Kotani, Joji (Frontiers in Pharmacology, 2022)
Burn injury is the leading cause of death and disability worldwide and places a tremendous economic burden on society. Systemic inflammatory responses induced by thermal burn injury induce severe involuntary loss of skeletal muscle, termed muscle wasting, which adversely affects the survival and functional outcomes of these patients. Currently, no drugs are available for the treatment of thermal burn-induced skeletal muscle wasting. Elevated levels of inflammatory cytokines, including interleukin-6 (IL-6), are important hallmarks of severe burn injury. The levels of signal transducer and activator of transcription 3 (STAT3)—a downstream effector of IL-6—are elevated with muscle wasting in various pro-catabolic conditions, and STAT3 has been implicated in the regulation of skeletal muscle atrophy. Here, we tested the effects of C188-9, which is a STAT3-specific signaling inhibitor, on skeletal muscle wasting in vivo induced by thermal burn injury and on C2C12 myotube atrophy in vitro after the administration of plasma from burn model mice. In mice, thermal burn injury severity dependently increased IL-6 in the plasma and tibialis anterior muscles and activated the STAT3 (increased ratio of phospho-STAT3/STAT3) and ubiquitin-proteasome proteolytic pathways (increased Atrogin-1/MAFbx and MuRF1), resulting in skeletal muscle atrophy and reduced grip strength. In murine C2C12 myotubes, plasma from burn mice activated the same inflammatory and proteolytic pathways leading to myotube atrophy. In mice with burn injury, the intraperitoneal injection of C188-9 (50 mg/kg) reduced STAT3 and ubiquitin-proteasome proteolytic pathway activation, reversed skeletal muscle atrophy, and increased grip strength. Similarly, pretreatment of murine C2C12 myotubes with C188-9 (10 μM) reduced the activation of the same inflammatory and proteolytic pathways, and ameliorated myotube atrophy induced by plasma taken from burn model mice. Collectively, our results indicate that the pharmacological inhibition of STAT3 signaling may be a novel therapeutic intervention for thermal burn-induced skeletal muscle wasting.